Legal Protection for Migrant Workers Under National and International Law - Muhammad Ilham Sumartoputra; T. Subarsyah Subarsyah; Siti Rodiah (Faculty of Law, Universitas Pekalongan, 2025)
The purpose of this study is to analyze and evaluate the implementation of legal protection for Indonesian Migrant Workers (PMI) according to national and international laws. This research aims to identify and understand the steps taken by the government in protecting migrant workers, especially those facing legal problems abroad, as well as explore effective and applicable legal protection models. Through this research, it is hoped that in-depth insights into policies and practices for the protection of migrant workers, as well as recommendations to strengthen existing legal protection in accordance with national and international standards. The research used is a normative research method with literature research involving the collection and analysis of primary, secondary, and tertiary legal materials. The results of the study show that the implementation of legal protection for Indonesian Migrant Workers (PMI) is regulated in national law through Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers, which includes the placement, rights, and obligations of PMI, as well as the responsibilities of various related parties. At the international level, the 1990 International Convention on the Protection of the Rights of All Migrant Workers and Their Family Members serves as the main legal instrument. To address the legal problems faced by migrant workers abroad, the Indonesian government, through BP2MI and the Ministry of Foreign Affairs, provides legal and advocacy services, including working with Indonesian advocates and negotiating with destination countries. An effective legal protection model includes the presence of BP2MI representatives in the countries of placement and the improvement of the quality and competitiveness of PMI through training and education, in line with the constitutional mandate to protect all Indonesian citizens.